Урван 26 ноября 2019 в 08:25

Найдите значение выражений :
1) (3^-2)^-1
2) (3^-1 * 2^3)^-1
3) (3^-1 + 2^3)^-1
4) (3^-1 - 2^3)^-1

1. (3^{-2})^{-1}=((frac{1}{3})^2)^{-1}=(frac{1}{9})^{-1}=9^1=9;
2. (3^{-1}*2^3)^{-1}=((frac{1}{3})^1*8)^{-1}=(frac{8}{3})^{-1}=(frac{3}{8})^1=0,375;
3. (3^{-1}+2^3)^{-1}=((frac{1}{3})^1+8)^{-1}=(frac{1}{3}+frac{24}{3})^{-1}=(frac{25}{3})^{-1}=(frac{3}{25})^1=0,12;
4. (3^{-1}-2^3)^{-1}=((frac{1}{3})^1-8)^{-1}=(frac{1}{3}-frac{24}{3})^{-1}=(-frac{23}{3})^{-1}=(-frac{3}{23})^1=-frac{3}{23}.
Вычисления
Для комментирования необходимо зарегистрироваться на сайте